Risk Factors of Hypertension in Reproductive Age Women in Kedai Durian Health Center, Medan, Indonesia - Friza Novita Sari Situmorang; Erna Mutiara; Fazidah Aguslina Siregar (Masters Program in Public Health, 2021)
Background: Hypertension is a global problem in the world. Data from the World Health Organization (WHO) in 2013 showed that deaths from complications of hypertension reached 9.4 million deaths worldwide. This study aims to determine the risk factors to the incidence of hypertension in women of reproductive age in Kedai Durian Health Center. Subjects and Method: This was a case control study carried out at Kedai Durian Health Center, Medan, Indonesia. A sample of 100 women of reproductive age was selected for this study. It consists of 50 women of reproductive age with hypertension and 50 women of reproductive age without hypertension. The dependent variable was hypertension. The independent variables were physical activity, obesity, and family history. Hypertension was measured by sphygmomanometer. The other data were collected by questionnaire. The data were analyzed by a multiple logistic regression. Results: Hypertension was associated with physical activity (OR=3.46;95% CI=1.52 to 7.90;p=0.003), obesity (OR=4.57;95% CI= 1.96 to 10.64 p<0.0001), family history (OR= 9.33;95% CI=720 to 23.41;p<0.0001), and fat consumption (OR=4.14;95% CI=1.79 to 9.57;p=0.001).Conclusion: Physical activity, obesity, family history, and fat consumption are associated with an increased risk of hypertension.